ANALYZING THE IMPLEMENTATION OF RAW MATERIAL INVENTORY PROCEDURE IN SUPPORTING THE EFFECTIVENESS OF INTERNAL CONTROL (STUDY AT PG NGADIREDJO KRAS – KEDIRI) - Nanik Sunarni (Fakultas Ilmu Administrasi Universitas Brawijaya, 2014)
Raw material inventory procedure is critical to maintain accuracy, reliable numbers for operation. Internal control on raw material inventory procedure is provided to ensure company has sufficient resources to meet customers’ needs without having too many goods. Physical count of raw material inventory is generally taken prior to issuance of balance sheet. The problems of study are: how is the implementation of raw material inventory procedure that has been applied by PG Ngadiredjo, how is the implementation of raw material inventory procedure in supporting the effectiveness of internal control that is conducted by PG Ngadiredjo. Type of research is descriptive research with case study approach. Result of research that implementation of raw material inventory procedure in supporting the effectiveness of internal control is good. But there are lacks that must be improved such: picture of effective wide and location sketch should be authorized by manager of quality control department, check sheet, felling schedule, instruction letter of felling and shipping, planning of cost estimation should be authorized by manager of plants department, contract agreement of sugarcane milling is authorized by chairman of KPTR to assure the reliable document and put functionary from quality control department to be placed in receiving post. Keyword: accuracy, reliable numbers, sufficient resources, customers’ needs, physical count Abstrak Prosedur persediaan bahan baku sangat penting untuk mempertahankan keakuratan dan jumlah bahan baku yang tepat untuk kegiatan operasi perusahaan. Pengendalian internal terhadap prosedur persediaan bahan baku dilaksanakan untuk memastikan bahwa perusahaan mempunyai sumber daya yang cukup untuk memenuhi kebutuhan konsumen tanpa memiliki terlalu banyak barang. Perhitungan fisik persediaan bahan baku pada umumnya dilaksanakan sebelum mengeluarkan neraca. Rumusan masalah pada penelitian ini adalah: bagaimana penerapan prosedur persediaan bahan baku yang sudah diterapkan oleh PG Ngadiredjo dan bagaimana penerapan prosedur persediaan bahan baku dalam mendukung efektivitas pengendalian internal di PG Ngadiredjo. Jenis penelitian ini adalah penelitan deskriptif dengan pendekatan studi kasus. Hasil dari penelitian ini adalah penerapan prosedur persediaan bahan baku dalam mendulung efektivitas pengendalian internal adalah baik. Tetapi ada beberapa kekurangan yang harus dibenahi seperti: gambar luas efektif dan denah lokasi seharusnya ditandatangani oleh manajer departemen quality control, check sheet, jadwal tebang, surat perintah tebang angkut, rencana anggaran biaya seharusnya ditandatangani oleh manajer departemen tanaman, kontrak perjanjian penggilingan tebu ditandatangani oleh ketua KPTR untuk menjamin dokumen yang dapat dipercaya dan menempatkan petugas dari departemen quality control untuk ditempatkan di pos penerimaan. Kata Kunci: Keakuratan, jumlah tepat, sumber daya cukup, kebutuhan konsumen, perhitungan fisik